Correction to: m6A mRNA methylation regulates CTNNB1 to promote the proliferation of hepatoblastoma - Li Liu; Jing Wang; Guifeng Sun; Qiong Wu; Ji Ma; Xin Zhang; Nan Huang; Zhixuan Bian; Song Gu; Min Xu; Minzhi Yin; Fenyong Sun; et al. (Molecular Cancer, 2020)
After the publication of this work [1], the authors noticed that the affiliations were incorrectly provided. Updated affiliation section is provided in this paper.